Mini ATX front end converter for solar application - Pedro, Rainville M.
The continuous demand for more efficient energy supply necessitates the development of technologies that harness the potential of alternative sources of energy. This paper presents a push-pull DC-to-DC converter whereby solar powered batteries, with 24-V output and 40A-hr capacity, were used as power source. A Current-mode control PWM integrated circuit (IC) was used to monitor and control the transistor currents, the output voltage and the duty ratio of the power switches. Experimental results were presented to have an agreement with the fundamental circuit analysis. Theoretical analysis and design methodology for a 24-V input, 225-W 300-V output laboratory prototype push-pull converter were discussed in this paper. The push-pull converter was used to replace the AC-to-DC converter in a power supply providing a cheaper alternative source of power to run personal computers.